THE POLITICAL SCENE, THE SOCIAL WORLD AND THE FIELD OF POWER - Sousa da Mota, Kênia (Revista Gênero e Interdisciplinaridade, 2024)
The objective of this article is to explore the theme “THE POLITICAL SCENE, THE SOCIAL WORLD AND THE FIELD OF POWER” within the scope of Brazilian education, based on the bias of IPEA PNAD with the text “Map of the hole & the search for solutions to get out of it”. The dialogue will guide some classic and contemporary authors such as OLIVEIRA (2000) and SANTOS (2015), which will open a range of conversations about the paths that must be followed for the transformation of quality Brazilian education. This analysis will have as its methodology bibliographical research, and in the procedures a research survey was carried out on the works that agree with the theme, later the works related to the theme were read.